2001
DOI: 10.1029/2000gl012088
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of sea ice; dependence on temperature and depth

Abstract: Abstract.We report an in situ experimental determination of the thermal conductivity of natural sea ice, a parameter required by models of climate and sea ice growth. The results obtained in the experiment differ in detail from the theoretically predicted values used by those models. In particular, we find that experimental results are lower than predicted, due to disorder in the crystalline structure of the ice. The reduction is nearly a factor of two near the top surface of the ice. Deeper in the ice, in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 18 publications
4
41
2
Order By: Relevance
“…We use a graphical finite difference scheme, which we have previously applied to sea ice measurements [ McGuinness et al , 1998; Trodahl et al , 2000, 2001], that does not require harmonic forcing and is insensitive to interthermistor calibration offsets. As for the other finite difference methods discussed in the preceding paragraph, we make the assumption of locally constant thermal properties for the space between adjacent thermistors.…”
Section: Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We use a graphical finite difference scheme, which we have previously applied to sea ice measurements [ McGuinness et al , 1998; Trodahl et al , 2000, 2001], that does not require harmonic forcing and is insensitive to interthermistor calibration offsets. As for the other finite difference methods discussed in the preceding paragraph, we make the assumption of locally constant thermal properties for the space between adjacent thermistors.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…The thermistor arrays are adapted from units custom‐built for measuring heat flow in first‐year sea ice [ McGuinness et al , 1998; Trodahl et al , 2000, 2001]. The body of the array is a 2‐m‐long, 0.25‐inch (6.35 mm) diameter, thin‐walled (0.2 mm) stainless steel tube.…”
Section: Instrumentation and Temperature Measurementsmentioning
confidence: 99%
“…k is generally assumed to be ~2 W m −1 K −1 for sea ice. Some research has suggested that the value may be as low as 1 W m −1 K −1 in the top 0.5 m of ice and potentially approaching 3 W m −1 K −1 near the bottom (Trodahl et al 2001), though the near-surface reduction has been suggested to be an artifact by later studies (Pringle et al 2006). Observed densities in the abovefreeboard part of ice cores are less than the lower portion of the cores, consistent with lower k near the surface; the near-bottom increase is thought due to brine conduction.…”
Section: Observed Impacts On Sea-ice Temperature and Growthmentioning
confidence: 99%
“…Sea ice is a semi-solid matrix of nearly pure ice crystals that incorporates bubbles of gas and brine inclusions in the form of pockets, tubes or as a network of brine channels (e.g., Weeks and Ackley 1986;Trodahl et al 2001). This labyrinth of brine inclusions constitutes the habitat of sympagic (sea-ice associated) organisms (including DMSP and DMSO producers), which live embedded in the viscous gel phase of the exopolymeric substances (EPS) produced by diatoms (Krembs et al 2002a).…”
Section: Effects On Sympagic Organismsmentioning
confidence: 99%